Metal interference alert guided septal approach with 3 catheter positions on intracardiac echocardiography for a near-zero fluoroscopy catheter ablation of atrial fibrillation. (December 2021) - Iwasaki, Yu-ki; Fujimoto, Yuhi; Ito-Hagiwara, Kanako; Oka, Eiichiro; Hayashi, Hiroshi; Yamamoto, Teppei; Murata, Hiroshige; Yodogawa, Kenji; Shimizu, Wataru
Abstract: Background: Attempting to minimize radiation exposure during catheter ablation of atrial fibrillation (AF) for patients, operators and medical staffs should be performed. This study aimed to investigate the feasibility and safety of a metal interference alert guided septal approach using 3 intracardiac echocardiography viewing positions for near-zero fluoroscopy AF ablation procedures. Methods/results: A total of 668 procedures among 608 consecutive patients with AF (67.2 ± 7.3 years, 408 males) who underwent catheter ablation were retrospectively evaluated and divided into 2 groups, near-zero group (n = 42) and conventional group (n = 595). In the near-zero group, a metal interference alert guided septal approach with 3 different catheter intracardiac echocardiography positions to minimize the fluoroscopy time was applied, and a left atrial access with 2 long sheaths from a single septal puncture without fluoroscopy was successfully achieved in 41 out of 42 cases. The total fluoroscopy time was significantly shorter in the near-zero group than that in the conventional group (0.5 ± 2.0 vs. 21.4 ± 12.9 min p < 0.0001). The total procedure time and time to the septal puncture were both significantly longer in the near-zero group than those in the conventional group (131.4 ± 40.2 vs. 116.6 ± 46.4p = 0.0453, 31.6 ± 9.2 vs. 19.9 ± 10.2 min, p < 0.0001), The ablation time did not differ between the 2 groups (Near-zero: 99.8 ± 41.0 vs. Conventional: 96.8 ± 44.3 min, p = 0.6663). There were no significant differences in the complication rate between the 2 groups (Near-zero: 0 vs. Conventional 14 case, p = 0.6151). Conclusion: A metal interference alert guided septal approach using 3 intracardiac echocardiography viewing positions was feasible and safe for a near-zero fluoroscopy catheter ablation of AF.